Protective effect of Fragaria ananassa methanolic extract on cadmium chloride (CdCl2)-induced hepatotoxicity in rats. (13th June 2017) - Elkhadragy, Manal F.; Abdel Moneim, Ahmed E.
Abstract: This study investigated the protective effect of Fragaria ananassa methanolic extract on cadmium chloride (CdCl2 )-induced hepatotoxicity in rats. CdCl2 was intraperitoneally injected at a dose of 6.5 mg/kg of body weight for 5 d with or without methanol extract of Fragaria ananassa (250 mg/kg). The hepatic cadmium concentration, lipid peroxidation, nitric oxide, glutathione (GSH) content, and antioxidant enzyme activities, including superoxide dismutase, catalase (CAT), GSH peroxidase, and GSH reductase, were estimated. CdCl2 injection induced a significant elevation in cadmium concentration, lipid peroxidation, and nitric oxide and caused a significant depletion in GSH content compared to controls, along with a remarkable decrease in antioxidant enzymes. Oxidative stress induction and cadmium accumulation in the liver were successfully ameliorated by F. ananassa (strawberry) pre-administration. In addition, the pre-administration of strawberry decreased the elevated gene expression of the pro-apoptotic Bax gene as well as the protein expression of caspases-3 in the liver of CdCl2 -injected rats. In addition, the reduced gene expression of anti-apoptotic Bcl-2 was increased. Our results show an increase in the expression of tumor necrosis factor α in the liver of rats treated with cadmium. In sum, our results suggested that F. ananassa successfully prevented deleterious effects on liver function by reinforcing the antioxidant defense system, inhibiting oxidative stress and reducing apoptosis.